2009
DOI: 10.1093/neuonc/nop013
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin regulates human glioma cell invasiveness and tumor growth in mice

Abstract: Human malignant glioma cells are characterized by local invasion. In the present study, we investigated the role of osteopontin (OPN) in the invasiveness of human glioma cells isolated from grade IV tumors. We found that the expression levels of OPN in these cell lines paralleled matrix metalloproteinase-2 (MMP-2) expression and cell invasiveness potential. When U87MG glioma cells (with a high-OPN expression level) were stably transformed with specific small hairpin RNA to knock down OPN expression, MMP-2 secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
67
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 35 publications
6
67
0
5
Order By: Relevance
“…Knockdown of OPN expression in a human GBM cell line by introduction of siRNA led to a reduction in cell proliferation, motility, and migration but no change in tumor-associated angiogenesis. Similar data were obtained by knockdown of OPN expression in human glioma cells (12). However, cleavage of OPN was not assessed in these studies (13).…”
supporting
confidence: 66%
“…Knockdown of OPN expression in a human GBM cell line by introduction of siRNA led to a reduction in cell proliferation, motility, and migration but no change in tumor-associated angiogenesis. Similar data were obtained by knockdown of OPN expression in human glioma cells (12). However, cleavage of OPN was not assessed in these studies (13).…”
supporting
confidence: 66%
“…Sox2 is identified in several glioma samples [49] and have an important role in the continuous proliferation of glioma cells [50] . Concerning the astrocytic properties of astrocytomas, vimentin is often referred as a marker for these brain tumors [51] , and it was described that its co-expression with nestin may serve as an indicator of an astrocytoma with an enhanced motility and invasive potential [52] . Mature astrocytic markers, such as GFAP, are also described to be expressed in glioma cells [53][54][55] , although Jan et al [51] showed that the malignant progression to a higher degree of invasiveness is associated with an increase in vimentin expression and a progressive loss of GFAP.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the astrocytic properties of astrocytomas, vimentin is often referred as a marker for these brain tumors [51] , and it was described that its co-expression with nestin may serve as an indicator of an astrocytoma with an enhanced motility and invasive potential [52] . Mature astrocytic markers, such as GFAP, are also described to be expressed in glioma cells [53][54][55] , although Jan et al [51] showed that the malignant progression to a higher degree of invasiveness is associated with an increase in vimentin expression and a progressive loss of GFAP. Besides the expression of immature and astrocytic cell markers, gliomas also express neuronal proteins such as β-III-tubulin [56,57] and MAP2 [58] , both indicators of a high-grade astrocytoma [58] .…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, osteopontin expression rates could be associated with histological grades, recurrence and survival of oligodendriomas and could be used as a predictive value. Osteopontin ekstrasellüler matrix ilişkili sialik asitten zengin fosfoglikoprotein yapısında integrin bağlayan bir protein olup kemik resorpsiyonu, yara iyileşmesi, doku yenilenmesi, immunolojik yanıtlar, vaskülarizasyon gibi normal fizyolojik süreçleri düzenler [3,4,5,6]. Aynı zamanda apopitoz, proliferasyon, adezyon, invazyon, metastazda da rol aldığı bilinmektedir.…”
unclassified
“…Aynı çalışmada glial tümörlerdeki invazyon kapasitesindeki farklılıkların osteopontin düzeyleri ile yakından ilişkili olduğu yönünde görüş belirtilmiştir [3,6,7].…”
unclassified